Optimal portfolio construction : a case in bursa Malaysia - Chin, Mei Han (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study investigates the adoption of portfolio construction in Malaysia stock market by using financial ratios such as economic value added (EVA), price earnings ratio (PER), book-to-market ratio (BM), size or market capitalization (MC) and dividend yield (DIV) from the year of 2009-2014. The aim of this study is to identify the optimum portfolio construction that generates maximum revenue for investors. Only 100 listed companies in Bursa Malaysia are being selected in constructing the portfolios - ATOP, BBOT, and CMID. The results of mean equality test derived are mostly insignificant results yet there is positive excess return (0.39%) found in portfolio with low performing DIV companies. The findings of this study also revealed that portfolio constructions which employ financial ratios are suitable for 2-3 years holding period investment. Most of the constructed portfolio show drastic drop of return after three years of holding period. Among the five portfolios, this paper suggests the best choice of portfolio construction for short term investment is to construct portfolio using DIV or MC